PENGARUH KEPADATAN YANG BERBEDA TERHADAP SINTASAN IKAN PENJA (FAMILI GOBIIDAE) DENGAN SISTEM TRANSPORTASI TERTUTUP - Nur, Muhammad; Irmayana; Dian Lestari; Syainullah Wahana; Rahmawati Tahir (Jurnal INSAN TANI, 2023)
This study aims to determine the effect of different densities on the survival of penja fish (Gobioidea) using a closed transportation system. This study used a completely randomized design (CRD) with 4 (four) treatments and three replications, namely treatment A (penja fish density 5 individuals/liter), treatment B (with a density of 10 individuals/liter), treatment C (with a density of 15 individuals/liter), and treatment D (with a density of 20 fish/liter). Parameters tested included survival and behavior and water quality parameters such as temperature, salinity and dissolved oxygen. Data analysis used ANOVA with a 95% confidence level. Based on the research results obtained, it can be concluded that with different densities in penja survival between treatments A, B, C and D during transportation and post-transportation, using a closed transportation system the results were not significantly different or each treatment achieved survival live 100% so that it can be used as a method of transporting penja fish. However, the efficiency of effective transportation of penja fish can be used up to a density of 20 fish/liter.